Validation of IRDFF-II library in VR-1 reactor field using thin targets. (August 2021) - Kostal, Michal; Losa, Evzen; Schulc, Martin; Simon, Jan; Bily, Tomas; Rypar, Vojtech; Mareček, Martin; Uhlíř, Jan; Czakoj, Tomáš; Capote, Roberto; Trkov, Andrej; Simakov, Stanislav
Highlights: Measurement of reaction rates in VR-1 reactor. Calculation of reaction rates in IRDFF-II. Validation of IRDFF-II against experiment. Testing of various approaches of evaluation of SACS. Abstract: Cross section data are fundamental quantities which affect the accuracy of all calculations in nuclear applications. A new dosimetry library IRDFF-II that contains cross section evaluations with full uncertainty quantification was developed by the International Atomic Energy Agency and released in January 2020 (https://www-nds.iea.org/IRDFF ). A previous version, IRDFF-1.05, was released in 2014 and experimental validation of the newly released cross section by spectrum averaged cross section (SACS) measurements is a high priority task. For such purpose, a neutron dosimeter set containing 5 target foils was activated in 2 independent experiments at the VR-1 reactor of the Czech Technical University in Prague. Care was taken to derive SACS with low uncertainties. New experimental evaluation method is in good agreement with previous approaches based on relative measurements using monitor foils. Good agreement of measured SACS and evaluated IRDFF-II cross sections is observed. Slight overestimation of evaluated ENDF/B-VIII.0 235 U(nth, f) PFNS above 10 MeV is discussed.